For a Historiography of the “Absences”: The Lived Experience and the Historical Present as Fundamental Categories for the Study of Latin American Peasant Subalternity - Alderete-Soto, P (Brazilian Society for History and Theory of Historiography, 2018)
During long passages in the history of Latin American historiography, a rather narrow conception of historical time, whose attributes of linearity, homogeneity and monoculturality are a direct derivation of the European Philosophy of History, has remained intact. With the exception of reflections from other fields of research (mainly sociology, philosophy and anthropology), historiography has eluded a positioning -from its own epistemic and methodological needs- that could virtually contribute to the recovery of the experiential diversity of the subalternized sectors (peasants): experiences that the Gordian knot of the modern Creole time has permanently condemned to the dark room of the traditional, the aftertaste and historical burden. In this article we aim to outline an alternative historical and methodological framework that, from a phenomenological, anthropological and present time foundation, allows a re-reading of the “historical event” and the “defiant anomaly” as central categories for overcoming this inheritance. © 2018 Brazilian Society for History and Theory of Historiography. All rights reserved.